Effect of Curing Condition on the Compressive Mechanical Behavior of Clayey Soil Stabilized with Liquid Polymer - Xiaoyong Zhu; Jin Liu; Jian Xue; Faming Zhang; Zhihao Chen; Guochang Hu; Canhui Jiang (International Journal of Polymer Science)
This study investigates the potential use of polyvinyl acetate emulsion in soil strengthening with emphasis on curing condition. Molded clay specimens treated with three polymer contents of 1%, 2%, and 3% (by the weight of dry soil) are cured in dry and humid environment, respectively. Unconfined compression tests are performed on the specimens after 1, 3, and 9 days of curing, and the results are compared with that for the untreated clay specimens. This comparison shows that polyvinyl acetate polymer can enhance soil mechanical properties. It was found that the compressive strength of soil-polymer composite increases significantly with the increase of polymer content and curing time in air-drying condition, which is 24% higher than that of plain soil after 9-day curing. The role of polymer treatment is to provide soil interparticle binding, which becomes particularly important in humid environments. In curing environments of high moisture, polymer-treated soils always have greater strength, but the effectiveness of polymer treatment decreases with polymer content. The scanning electron microscopies indicate that soil structure is reinforced mostly by three-dimensional interparticle polymeric bridges. The tension in polymeric threads and textiles provides the interparticle bonding that prevents the development of cracks.